Development of bioanalytical parameters for standardization of Azadiracta indica - Patel D.K.; Dhanabal S.P. (My University, 2025)
Objective: To develop noval bioanalytical parameters for standardization of Azadiracta indica (A. indica) extract. Methods: In the present investigation, preliminary phytochemical analysis, total phenol, flavonoid, solubility test, heavy metal analysis, antimicrobial study and quantitative analysis through HPTLC method were performed. Results: Preliminary phytochemical analysis showed the presence of carbohydrate, tannin, steroid, triterpenoid, glycoside, saponin and flavonoid in the extract. Loss on drying, total ash and solubility in water was found to be 4.60%, 5.61% and 91.0%. Total flavonoid and phenol content was found to be 1.8% and 14.08% w/w. The content of quercetin, rutin and gallic acid in A. indica was found to be 0.93%, 1.22% and 0.33% w/w respectively. Further the level of heavy metal content and microrganism were found to be in the safe level. Conclusions: In future, these bioanalytical parameters could be used as important tool for the standardization of A. indica extract. © 2013 Hainan Medical College.